Pengaruh Harga, Kualitas Makanan Terhadap Kepuasan Pelanggan Studi Kasus Mie Gacoan - Ningtiyas, Deby (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2024)
AbstractThis study aims to evaluate the impact of price and food quality on customer satisfaction at Mie Gacoan. The research method used is a quantitative approach with a survey involving 30 respondents. Data were collected through a questionnaire that included questions about perceptions of price, food quality, and customer satisfaction levels. Data analysis was performed using simple linear regression. The results of the study indicate that both price and food quality significantly influence customer satisfaction. Food quality has a stronger impact compared to price. Therefore, to enhance customer satisfaction, Mie Gacoan is advised to focus more on improving food quality while maintaining affordable prices.